Challenges faced Muslim women leaders in higher education - Almaki, Samah Hatem; Silong, Abu Daud; Idris, Khairuddin; Abd. Wahat, Nor Wahiza (Mediterranean Center of Social and Educational Research, 2016)
The role of Muslim women in the society has changed dramatically in the last 20 years. As a result of the increasing prevalence of women at all levels of education and in different fields of employment and aspects of public life, women now seek to achieve the highest leadership roles in all sectors and as well as in higher education sector and to participate on the various positions and in the decision-making process in public and private sectors. However, women who strive to assume the leadership positions are facing multiple challenges and many times give up because they become overwhelmed in dealing with multiple barriers. Therefore, the objective of this qualitative, phenomenological article is to probe into challenges that Muslim women academic leaders face both in their leadership position and in their communities by using semi- structured interview with some Muslim women academic leader. It is ascertained through the study that Muslim women academic leaders find it hard to make a significant impact in terms of knowledge due to the attitude of society toward women leaders and many women feel that society is still male dominated, and men are not accepted the idea of women holding senior posts, as well as personal and organization challenges. At the end, the article recommends different strategies to overcome these challenges and develop women in the position of leadership.